Magnetic Solid-Phase Extraction of Drugs and Pesticides from Human Plasma Using COOH-mMWCNTs. Issue 9 (21st January 2021) - Moon, Heesung; Park, Jiwon; Hwang, Jinwoo; Chung, Heesun
Abstract: Carbon nanotubes (CNTs) are useful for extracting chemical compounds due to their properties, such as surface area and the potential for chemical modification. Especially the formation of CNTs with carboxylic acid functional group makes them disperse in water-based samples and have strong interaction forces with cationizable analytes. Based on these features, carboxylic acid functionalized multi-walled CNTs (COOH-MWCNTs) have been used as extraction sorbents. CNT can also be gathered using an external magnet by forming complex with iron oxide (Fe3 O4 ) magnetic nanoparticles (MNPs). In this study, COOH-MWCNTs with MNPs were subjected to magnetic solid-phase extraction (mSPE) in order to extract the targeted substances such as diphenhydramine, doxylamine, tramadol, escitalopram, zolpidem, diphenamid, paclobutrazol, hexaconazole, cyproconazole and mepronil from human plasma samples. The following five factors were optimized: (i) the ratio of COOH-MWCNTs to MNPs as a sorbent from 1:1 to 1:4; (ii) sorbent amount starting from 12.5 to 75%; (iii) sample pH tested pH 2 to pH 10 with 1 N hydrochloride and 1 N sodium hydroxide; (iv) agitating time from 0 to 4 min and (v) elution solvent. Limit of detection of 10 targeted substances in human plasma were in the range of 0.1–0.4 mg/L. The recovery of targeted substances (except diphenamid) in human plasma was 73.06–110.28% for intra-day and 83.00–107.70% for inter-day and the precision (relative standard deviation, %) in human plasma was 0.3–13.3% for intra-day and 2.9–15.6% for inter-day. The method was applied to nine authentic biological samples from overdose patients in the emergency room of Chungnam National University Hospital. The performance of mSPE was compared with the liquid–liquid extraction method using ethyl acetate. The results showed that the newly developed method in this study can be used for screening analysis in forensic and clinical toxicology.